2017
DOI: 10.1007/s40519-017-0413-x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-relationship of serum leptin levels with selected anthropometric parameters among a non-diabetic population: a cross-sectional study

Abstract: A descriptive cross-sectional study, Level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
3
5
0
1
Order By: Relevance
“…Circulating leptin concentrations are known to reflect total body fat and to be higher in females than in males. In our patients, serum leptin in men and women did not differ, and its levels were comparable with those of control subjects in previous studies [33,34]. Leptin was lower in children, as could be expected.…”
Section: Discussionsupporting
confidence: 88%
“…Circulating leptin concentrations are known to reflect total body fat and to be higher in females than in males. In our patients, serum leptin in men and women did not differ, and its levels were comparable with those of control subjects in previous studies [33,34]. Leptin was lower in children, as could be expected.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with greater leptin gene expression and peptide content in the women fundus, in our study, we noticed significantly higher (more than three times) serum leptin levels in women than in men. Similarly higher hormone levels in the women's blood were described by Ostlund et al ., Kennedy et al ., and Anusha et al …”
Section: Discussionsupporting
confidence: 80%
“…The level of leptin in the human body depends on anthropometric parameters, such as body mass index (BMI), weight, age, or sex . Literature data show that serum leptin concentration is several times higher in women than in men .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the association between age and adipokines’ levels it is not unambiguous. For example, a cross-sectional study carried out among 226 apparently healthy subjects showed that serum leptin level was not correlated with age in men, whereas in female a significant positive correlation was found [ 53 ]. In another study included 147 patients with T2DM no significant correlation between adiponectin and any clinical parameters, including age, was found [ 54 ], whereas Tingelstad et al [ 55 ] in the study including 331 members of the regular Canadian Armed Forces showed that adiponectin was increasing with increasing age.…”
Section: Discussionmentioning
confidence: 99%